Perilaku dan Motivasi Anak Angkringan dalam Judi Online di Indonesia - Ningsih, Susiyati; Farihah, Lailatul; Prasetya, Benny (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2025)
This study is about "The Behavior and Motivation of Angkringan Children in Gambling (Case Study in Laweyan Village)." The research aims to identify and analyze the behavior and motivation of children working at angkringan (street food stalls) in relation to their involvement in gambling activities in Laweyan Village. The study employs a case study approach to gain a deep and comprehensive understanding of the various social and psychological factors influencing children's engagement in gambling. Data collection was carried out through detailed participant observation, in-depth interviews with various relevant parties, and analysis of pertinent documents.The findings reveal that economic factors are the primary drivers for children to engage in gambling, with urgent financial needs compelling them to seek alternative income sources. The social environment also plays a significant role, particularly in terms of peer influence and community norms that do not strongly condemn gambling activities. The lack of supervision and attention from parents further reinforces children's involvement in these activities.The study concludes that holistic and coordinated interventions from the government, educational institutions, and social organizations are crucial in addressing this issue.